TANGGUNG JAWAB DOKTER DENGAN PASIEN DALAM PERJANJIAN TERAPEUTIK (Studi Di Rumah Sakit Islam Namira) - Wahyudi, Ardian (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
This research aims to find out and analyse the doctor responsibilities with patient in the therapeutic agreement in namira Islamic hospital.  Health is one element of general welfare that must be realized. Health must also be realized in accordance with Law Number 36 of 2009 concerning Health, The agreement or therapeutic agreement that occurs between a doctor and a patient is not only in the field of medicine, but is much broader. The specificity of this agreement lies in the agreed object, namely in the form of the most appropriate effort or therapy to cure patients in health facilities throughout Indonesia, especially at the Namira Selong Islamic Hospital. This research aims to find out what kind of responsibility doctors have with patients and what factors exist in therapeutic agreements that do not comply with the law for general adult patients at Namira Islamic Hospital. This research uses an empirical normative legal method with a case and statutory approach carried out at the Namira Islamic Hospital, especially for general adult poly-ophthalmic patients. Based on the results of research, interviews and findings in the field, it was found that it had been implemented well, but there needed to be some development and innovation to make activities in the field easier.